2022
DOI: 10.1017/s0033291722002392
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural brain differences in bipolar disorder: a multimodal meta-analysis of neuroimaging studies

Abstract: Background Numerous studies of resting-state functional imaging and voxel-based morphometry (VBM) have revealed differences in specific brain regions of patients with bipolar disorder (BD), but the results have been inconsistent. Methods A whole-brain voxel-wise meta-analysis was conducted on resting-state functional imaging and VBM studies that compared differences between patients with BD and healthy controls using Seed-based d Mapping with Permutation of Subject Images software. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 119 publications
1
16
0
Order By: Relevance
“…For example, Wang Ying et al . observed an increase in functional function in the left middle lobe, right brain, and right upper extremity of bipolar disorder patients and a decrease in the resting activity of the crotch lobe [36]. This is analogous to our results, but there are quite opposite consequences depending on whether sample subjects, disease subtypes, drug interference, or genetic factors are interfering.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For example, Wang Ying et al . observed an increase in functional function in the left middle lobe, right brain, and right upper extremity of bipolar disorder patients and a decrease in the resting activity of the crotch lobe [36]. This is analogous to our results, but there are quite opposite consequences depending on whether sample subjects, disease subtypes, drug interference, or genetic factors are interfering.…”
Section: Discussionsupporting
confidence: 88%
“…After treatment, these signals in the patient's brain and node center showed normalization [35]. Furthermore, a multimodal meta-analysis found patients with bipolar disorder displayed increased resting-state functional activity in the left middle frontal gyrus, right inferior frontal gyrus (IFG) extending to the right insula, right superior frontal gyrus and bilateral striatum, and sMRI meta-analysis showed that patients with bipolar disorder displayed decreased VBM in the right IFG extending to the right insula, STG, left superior frontal gyrus (medial prefrontal cortex), left thalamus, and right fusiform gyrus [36]. When degree centrality values in the left parahippocampal gyrus were used as a biomarker to differentiate between bipolar mania patients and healthy controls via an SVM approach, the associated accuracy (83.33%), specificity (85.51%), and sensitivity (88.41%) values suggested that reduced degree centrality values in the left parahippocampal gyrus may represent an effective biomarker of bipolar mania.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that the connectivity between precuneus and fusiform was significantly lower in both of ADHD and BD group than HG. Precuneus and fusiform, as the core regions of default mode network (DMN) and visual processing network (VPN), showed altered resting-state functional connectivity as well as decreased grey matter in both ADHD and BD group (Chen et al, 2022; Kucyi et al, 2015; Sutcubasi et al, 2020). More specifically, the intra-network connectivity between DMN and VPN exhibited a strong contribution to emotion classification and sustained emotional experience during naturalistic contexts (Xu et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The authors found decreased volume in the post-central gyrus, right paracentral lobule, and left superior temporal gyrus. Chen et al [25] noted that individuals with BSDs displayed structural alterations in some areas, particularly the left superior temporal and post-central gyri. Alterations in these areas of the brain may contribute to auditory hallucinations, difficulty ascertaining the emotions of others, risk-taking, and emotional dysregulation [25].…”
Section: Stress Shift Work and Sleepmentioning
confidence: 99%